DIMENSI BERNALAR KRITIS DALAM PEMBELAJARAN MENULIS TEKS BERITA PADA MODUL AJAR DI SMPN 25 KOTA JAMBI - Afriza, Yunita; Rustam, Rustam; D, Yusra (Universitas Negeri Makassar, 2024)
The aim of this research is to determine the application of critical reasoning dimensions in learning news texts in open modules at SMPN 25 in Jambi City. The approach in this research uses a qualitative approach with a case study-type approach. Data collection was carried out by means of interviews, observation, and documentation in the field. The results of this research show the application of the critical reasoning dimension, where students are required to be able to determine the truth in a problem. Students must be able to think critically in dealing with a problem. The critical reasoning dimension in the text makes students able to think critically through their reasoning. Students are able to process and disseminate the problems they face into news based on facts in the field discovered by students. Students are also able to write opinion sentences and fact sentences in the news. The application of the critical reasoning dimension runs according to the steps contained in the teaching module. By applying this dimension, students are able to think critically when facing problems.